SKILLS AND LOWER WAGES: A STUDY ON FOREIGN DOMESTIC WORKERS IN MALAYSIA. - Kadiresan, Vimala; Begum, Mehrunishah; Hamind, Bathusha; Nadaraja, Dineswary (IJRDO - Journal of Business Management, 2016)
This paper explores on the reasons for Malaysian households in employing foreign domestic workers. Throughout the past years, migrant workers have been hired in Malaysia for various sectors whereby many companies are said to prefer hiring them instead of local workers. Foreign workers are categorized into skilled and unskilled workers. Malaysia’s rapid economic growth, the result of higher standard of living and the increasingly common intention of Malaysian women to follow their own career aspirations have risen the demand of employing a domestic worker which will take over the household chores and take care of the children and elderly (Orange, Seitz, & Kor, 2012 and Devadason & Meng, 2013). In Malaysia, there are about 2.1 million registered foreigners whereby the majority of these foreign workers are divided into skilled workers and unskilled workers (theSundaily, 2014). Availability of workers to perform domestic works are rather scarce in Malaysia and deemed comparatively costlier than foreign domestic workers. Most of the local workers are employed in manufacturing and service industries instead of households. In this case, foreign workers are more favourable in today’s situation as many factors which revolves argument on what influences the managers to recruit foreign domestic workers over local workers. Based on Forde and MacKenzie’s (2009) research, a few factors were chosen for this study such as shortage of supply with job experience, shortage of supply with required skills and lower cost in wages. Employers would always prefer workers that have experience readily available in doing the job as it will help them save cost for training and development. Besides, foreign domestic workers are known as fast leaners with high adaptability as their initiative to improve is higher and will not to be dependent on local workers thus, enabling the job to be done without asking too many question or bothering others (Abdul Rahman et al, 2012). The recruitment of foreign domestic workers is vital for households to hire them here in Malaysia due to three factors mentioned earlier. The shortage of supply in the workforce from local workers with required skills and experience will further invite more need for foreign domestic workers. Furthermore, local workers tend to ask for higher salary for a job compared to a foreign domestic worker who is willing to.Malaysia can only hire from certain countries approved by Malaysian government and the eligibilities according to countries have been stipulated (imi, 2014.